Climate change, water and agriculture linkages in the upper Indus basin: A field study from Gilgit-Baltistan and Leh-Ladakh - Tuladhar, S.; Hussain, A.; Baig, S.; Ali, A.; Soheb, M.; Angchuk, T.; Dimri, A. P.; Shrestha, A. B. (Frontiers in Sustainable Food Systems, 2023)
The Indus is one of three largest river systems emerging from the Hindu-Kush Himalaya (HKH). In the Upper Indus Basin (UIB), water resources, agriculture and livelihoods are highly vulnerable to climate change induced hazards and risks. Present study investigates impacts of climate change on water availability, agriculture and livelihoods based on perception data collected through focus group discussions and key informant interviews from selected study sites in Gilgit-Baltistan and Leh-Ladakh subregions of the UIB. Findings revealed that climate change is inducing both direct and indirect impacts on water availability, agriculture, and livelihoods. Local people reported that changes in precipitations patterns, temperature and timing of seasons, and increased incidence of crop pest attacks are resulting in the decline of crop and livestock productivity (direct impacts). Climate change is also impacting productivity indirectly through degradation of rangelands/pastures and water variability in traditional irrigation systems. Local people are taking diverse adaptation measures to cope with climate change impacts. These measures include revival of less water intensive traditional crops, start of enterprises and value chain developments in Gilgit-Baltistan, and improvement in water management practices and integration of traditional agricultural products with tourism in Leh-Ladakh. Some adaptation measures are likely to have negative impacts on sustainability of local agriculture. For instance, inorganic agricultural practices in Gilgit-Baltistan, and unplanned shift to water intensive crops and improved breeds of livestock in both Gilgit-Baltistan and Leh-Ladakh. Based on findings, this study suggests establishing a learning mechanism for local communities through collaboration of local institutions from both sides of border and people to people connections.